2022
DOI: 10.20525/ijrbs.v11i1.1546
|View full text |Cite
|
Sign up to set email alerts
|

Job demands-resources, work engagement, and organizational commitment

Abstract: This study presents the Job Demands-Resources (JD-R) model to investigate employees’ organizational commitment. The purpose of this study is to examine the effect of job demands and job resources on organizational commitment, as well as the mediating effect of work engagement, in the context of Indonesian state-owned enterprises. Data were gathered using a questionnaire from 115 employees of a state-owned enterprise. Partial Least Squares - Structural Equation Modeling (PLS-SEM) was performed to analyze data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
2
3
0
Order By: Relevance
“…The results of this study also support the research of Priyono et al (2022) employees of BUMN companies in Indonesia that job demand has a significant negative effect on organizational commitment, where the higher the job demand, the lower the organizational commitment. In line with the findings of Widyawaty et al (2022) on employees of national private companies in Indonesia that job demand has a significant negative effect on organizational commitment.…”
Section: Resultssupporting
confidence: 86%
“…The results of this study also support the research of Priyono et al (2022) employees of BUMN companies in Indonesia that job demand has a significant negative effect on organizational commitment, where the higher the job demand, the lower the organizational commitment. In line with the findings of Widyawaty et al (2022) on employees of national private companies in Indonesia that job demand has a significant negative effect on organizational commitment.…”
Section: Resultssupporting
confidence: 86%
“…Furthermore, Doogajudhur & Dell (2019) also obtained a negative effect of job demand on the organizational commitment of 400 permanent employees in various industrial sectors in Mauritius. The results of this study also support the research of Priyono et al (2022) employees of BUMN companies in Indonesia that job demand has a significant negative effect on organizational commitment, where the higher the job demand, the lower the organizational commitment. In line with the findings of Widyawaty et al (2022) on employees of national private companies in Indonesia that job demand has a significant negative effect on organizational commitment.…”
Section: Resultssupporting
confidence: 86%
“…On the other hand, they extrinsically facilitate the achievement of work goals, becoming an indispensable tool for reaching professional targets. Thus, it is confirmed that nurses with a stronger sense of professional self-efficacy can face work challenges with more confidence and skill, which, in turn, can increase their job engagement ( 61 , 84 ).…”
Section: Discussionmentioning
confidence: 84%
“…Work engagement also exerts a significant influence on key aspects like the intention to leave the job, job adaptation, and organizational performance. Engaged employees tend to exhibit greater loyalty and both affective and normative commitment to their organization, resulting in better performance at both individual and organizational levels ( 61 ). Furthermore, work engagement can be an indicator of the frequency of job absences, reflecting higher motivation and better overall health ( 10 ).…”
Section: Introductionmentioning
confidence: 99%